A Question of Value(S): Political Connectedness and Executive Compensation in Public Sector Organizations. Issue 3 (27th May 2018) - Meyer, Renate E.; Höllerer, Markus A.; Leixnering, Stephan
ABSTRACT: While the de-politicization of public sector management was a core objective of past reform initiatives, more recent debates urge the state to act as a strong principal when it comes to public sector unity and policy coherence, and consequently make a case for reinvigorating links between the political and managerial sphere. Using data from Austrian public sector organizations, we test and confirm the causal relationship of political connectedness of board members and executive compensation. Differentiating between value-based and interest-based in-groups, we suggest that only value-based political connectedness has the potential to restore patronage as a control instrument and governance tool. Self-interested and reward-driven patronage, on the other hand, indicated by a strong association of political connectedness and executive pay, refers to the type of politicization that previous public sector reforms promised to abolish.